MENGUJI MODEL HUBUNGAN ANTARA ORGANIZATION-BASED SELF ESTEEM TERHADAP ORGANIZATONAL CITIZENSHIP BEHAVIOR; SELF EFFICACY SEBAGAI VARIABEL PEMEDIASIAN - Susi Widjajani; Joko Wiyono; Mia Rahma Romadoni (Optimum: Jurnal Ekonomi dan Pembangunan, 2014)
Organizational behavior is a refl ection of the attitudes and behaviors of employees who believed based on the perception of the individual to improve their performance. The purpose of study will describe the infl uence of organization-based self-esteem (OBSE) on organizational citizenship behavior (OCB) mediated self effi cacy. The research was quantitative methode and to collect data using instruments measuring instrument adapted from self-effi cacy (Bandura, 1997), OBSE (Pierce, Gardner, Cummings, & Dunham, 1989, 1993) and OCB (Williams & Anderson, 1991). Samples of the research were hospital employees, group D both medical and nonmedical employees in the region of Yogyakarta Province. Results of the factor analysis with SEM using AMOS version 18, describes relationship OBSE on OCB both directly and mediated by self-effi cacy in the work environment within the scope of the valueattitude- behavior.